2012
DOI: 10.1038/oby.2011.136
|View full text |Cite
|
Sign up to set email alerts
|

Serum γ‐Glutamyltransferase: Independent Predictor of Risk of Diabetes, Hypertension, Metabolic Syndrome, and Coronary Disease

Abstract: Serum γ‐glutamyltransferase (GGT) is associated with oxidative stress and hepatic steatosis. The extent to which its value in determining incident cardiometabolic risk (coronary heart disease (CHD), metabolic syndrome (MetS), hypertension and type 2 diabetes) is independent of obesity needs to be further explored in ethnicities. After appropriate exclusions, a cohort of 1,667 adults of a general population (age 52 ±11 years) was evaluated prospectively at 4 year's follow‐up using partly Cox proportional hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
74
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 26 publications
(44 reference statements)
11
74
0
2
Order By: Relevance
“…Oxidative stress was shown to play important roles in many phases of atherosclerosis [3]. Elevated serum GGT levels have been shown to be associated with development of diabetes mellitus (DM), hypertension (HT) and metabolic syndrome [5][6][7]. The relationship between GGT levels and CAD is established in many studies [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress was shown to play important roles in many phases of atherosclerosis [3]. Elevated serum GGT levels have been shown to be associated with development of diabetes mellitus (DM), hypertension (HT) and metabolic syndrome [5][6][7]. The relationship between GGT levels and CAD is established in many studies [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that there was a close relationship between increased serum GGT levels and other prognostic factors, such as hypertension, metabolic syndrome, diabetes, dyslipidemia (6,36). But we do not have clearly information about an association between GGT and known ischemic heart disease risk factors.…”
Section: Discussionmentioning
confidence: 72%
“…The GGT activity has been observed in coronary atherosclerotic plaques (4). Several studies demonstrated that an elevated serum GGT activity can be used as a marker for increased oxidative stress in humans (5,6). In addition, serum GGT was an independent risk factor for the diabetes mellitus, stroke and hypertension (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Present findings and those of others discussed indicate that any relevant degree of pro-inflammatory state/oxidative stress offsetting the balance of anti-inflammatory processes may be prominently involved in the development of prehypertension or hypertension, be it low levels or dysfunctional high levels of apoA-I, HDL particles or adiponectin, or elevated concentrations of CRP, apoB or gamma-glutamyltransferase (32). High levels of pro-inflammatory apoA-I may thereby be accounted for a prospective association with diabetes, CHD and prehypertension.…”
Section: Discussionmentioning
confidence: 94%